Findings from the Clinical Information Systems Perspective - Ganslandt, T.; Hackl, W.O.; Section Editors for the IMIA Yearbook Section on Clinical Information Systems (Yearbook of Medical Informatics, 2015)
Objective: To summarize recent research and to propose a selection of best papers published in 2014 in the field of Clinical Information Systems (CIS).Method: A query with search terms from the Medical Subject Headings (MeSH) catalog as well as additional free text search terms was designed to identify relevant publications in the field of clinical information systems from PubMed and Web of Science®. The retrieved articles were then categorized in a multi-pass review carried out separately by the section editors. The final selection of 15 candidate papers was then peer-reviewed by Yearbook editors and external reviewers. Based on the review results the four best papers were then selected at the best papers selection meeting with the IMIA Yearbook editorial board.Results: The query was carried out in mid-January 2015, yielding a combined result set of 1525 articles which were published in 722 different journals. Among these articles two main thematic sections were identified: i) Interoperability from a syntactical and semantic point of view as well as from a long-term preservation and organizational/legal point of view and ii) secondary use of existing health data in all its shades. Here, patient safety was a major scope of application.Conclusions: CIS have become mature over the last years. The focus has now moved beyond data acquisition for just supporting the local care workflows. Actual research efforts in the CIS domain comprise the breakdown of information silos, the reduction of barriers between different systems of different care providers and secondary use of accumulated health data for multiple purposes.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; clinical information systems